Twining-Hadley Incorporated - Elias, Jaan; Rouwenhorst, K. Geert; Thomas, Jacob, active 2018 (London : Yale School of Management, 2018)
In February 2018, Jessica Austin, a recently promoted senior analyst in the Twining-Hadley Incorporated (THI) CFO's office, was asked to calculate the company's Weighted Average Cost of Capital (WACC) for the coming budgetary cycle. Austin was eager to prove herself in her new job and eagerly set about the task. THI (a fictitious company modeled after real-life examples) was a large consumer goods and healthcare company, with a market cap in excess of $300 billion. With over 112,000 employees located in facilities across the globe, the company sold its products in nearly every country in the world. THI organized its businesses into three segments reflective of the markets it served: Consumer, Pharmaceutical, and Medical Devices.
Originally Published InElias, J., Rouwenhorst, K. G., & Thomas, J. (2018). Twining-Hadley Incorporated. 18-020. New Haven, CT: Yale School of Management, Yale University. Retrieved from: http://vol12.cases.som.yale.edu/twining-hadley-incorporated.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Capital costs -- Case studies; Big business -- Finance -- Case studies